Relationships Between First-Year Student Resilience and Academic Stress - David W. Nordstokke; Yvonne Hindes (Behavioral Sciences)
Academic stress is a prevalent issue among university students, with significant implications for mental health and academic performance. This exploratory study examined whether academic stress could be predicted from resilience sub-factors based on a three-factor model of resilience. An initial sample of 70 first-year university students completed self-report measures assessing mastery, relatedness, emotional reactivity, and academic stress. After accounting for missing data, 68 participants were female (65%; n = 44) and 35% (n = 24) were male. The mean age of the participants was 18.52 years, with a standard deviation of 1.26. Multiple regression analysis revealed that the sub-factors of mastery, relatedness, and reactivity were significant predictors of academic stress. Specifically, self-efficacy and perceived support were negatively associated with academic stress, and emotional sensitivity was positively associated with academic stress. The results have important implications for interventions aimed at reducing academic stress that focus on these resilience sub-factors could offer an effective approach for improving outcomes in transitioning students. Interventions such as cognitive training and mindfulness-based programs may strengthen students’ executive function difficulties, thereby improving their ability to cope with academic stress and foster resilience.